2017
DOI: 10.5935/abc.20170067
|View full text |Cite
|
Sign up to set email alerts
|

Hypertriglyceridemic Waist Phenotype and Changes in the Fasting Glycemia and Blood Pressure in Children and Adolescents Over One-Year Follow-Up Period

Abstract: BackgroundThe hypertriglyceridemic waist (HTW) phenotype is defined as the simultaneous presence of increased waist circumference (WC) and serum triglycerides (TG) levels and it has been associated with cardiometabolic risk in children and adolescents.ObjectiveThe objective was to evaluate the influence of HTW phenotype in the fasting glycemia and blood pressure in children and adolescents over one-year follow-up period.MethodsIt is a cohort study involving 492 children and adolescents from 7 to 15 years old, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Others [ 3 ] reported a case of partial tear of the latissimus dorsi muscle in a basketball player, in which the sonogram showing muscle thickening, echogenic enhancement, partial interruption of the echogenic continuity of the muscle fibers, and intramuscular hematoma formation was an important manifestation, and the echogenic nature of the hematoma could change with the migration of the injury time, as shown in Figure 1 . A complete tear is characterized by a complete disruption of the muscle echogenic continuity, with the broken end being hyperechoic and retracted to form a “mass,” which is surrounded by a larger hematoma, forming a typical “bell and tongue sign” [ 4 ]. When the low back muscle is violently impacted or crushed, it can cause muscle contusions and diffuse swelling of the damaged muscle, which can bleed under the extramuscular membrane or within the muscle to form a hematoma.…”
Section: Introductionmentioning
confidence: 99%
“…Others [ 3 ] reported a case of partial tear of the latissimus dorsi muscle in a basketball player, in which the sonogram showing muscle thickening, echogenic enhancement, partial interruption of the echogenic continuity of the muscle fibers, and intramuscular hematoma formation was an important manifestation, and the echogenic nature of the hematoma could change with the migration of the injury time, as shown in Figure 1 . A complete tear is characterized by a complete disruption of the muscle echogenic continuity, with the broken end being hyperechoic and retracted to form a “mass,” which is surrounded by a larger hematoma, forming a typical “bell and tongue sign” [ 4 ]. When the low back muscle is violently impacted or crushed, it can cause muscle contusions and diffuse swelling of the damaged muscle, which can bleed under the extramuscular membrane or within the muscle to form a hematoma.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that simultaneous measurement of WC and fasting TG could be used as an inexpensive screening method to identify men at a high risk for the atherogenic metabolic triad and cardiovascular diseases 14 . Since then, more studies have confirmed that HTWP is closely related to the occurrence of cardiovascular diseases 19 , 20 . With further supporting research, HTWP has been considered an inexpensive and effective marker reflecting visceral (intra-abdominal) obesity and metabolic disorders.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, researchers have suggested that WC and TG level should be included as clinical indicators of visceral fat accumulation 17 . Substantial studies have shown that HTWP may also be used as an indicator for the early diagnosis of coronary heart disease, hypertension 18 – 20 , metabolic syndrome (MetS) 21 , and T2DM and its complications 19 , 22 25 in adults 26 30 and children 21 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, lower percentages have also been documented in the scientific literature. In a cohort with students from a city in Bahia involving children and adolescents, Costa et al 12 found a prevalence of 10.6%. In studies conducted by Pereira et al 11 and Conceição-Machado et al, 8 the phenotype was prevalent only in adolescents, with 6.4 and 7.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…9 In 2000, Lemieux et al developed one of the first studies involving HTGW with a sample of Canadian male adults, finding high agreement between this index and the atherogenic metabolic triad. 10 Nevertheless, despite the lack of studies involving individuals with T1DM nationwide, the literature has presented research with several populations, including children 11 and adolescents, 8,12 indicating a scenario in which CVDs represent the main cause of morbidity and mortality, affecting increasingly younger individuals and significantly reducing productive life. Thus, this study aimed to evaluate the frequency of the HTGW phenotype and its associated factors in children and adolescents with T1DM.…”
Section: Introductionmentioning
confidence: 99%